Commuters opinion on public transport services in mega cities: the case of Istanbul buses - Genç, Atakan; Alkhaledi, Khaled; Sağlam, Sait; Bendak, Salaheddine (Frontiers in Sustainable Cities, 2023)
Using public transport is an important part of daily routine of many people in large cities and consumes considerable time and financial resources. Enhancing public transport can help in encouraging less use of privately owned motor vehicles and, therefore, in emitting less greenhouse gases. Hence, there is a need to improve public transport and make it more attractive than private motor vehicles. This study aims to assess commuters opinion on several aspects related to using public buses in Istanbul with the ultimate aim of making them more attractive than private motor vehicles. A total of 620 randomly selected bus commuters responded to a questionnaire specially prepared for this purpose. Satisfaction rates with most aspects related to public buses were found to be high. Nevertheless, non-parametric test results revealed that female commuters recorded significantly lower satisfaction rates than male commuters on many aspects related to public buses. Results also revealed that a significant minority of commuters walk for long distances to the nearest bus stop or wait for very long times for the next bus to come. Moreover, results revealed that commuters of older ages and higher income levels recorded significant higher satisfaction rates than others.Results also show that the majority of commuters support increasing bus fees during peak hours in order to minimise crowdedness during these hours. Implications of these results for decision makers in megacities on ways to encourage the use of public buses are discussed at the end.